ESTIMATE OF PHENOTYPIC AND GENOTYPIC VARIATION, HERITABILITY AND CORRELATIONS ON NINE DURUM WHEAT CULTIVARS (Triticum durum Desf.) UNDER LIMITED RAINFALL CONDITIONS - Mohammed Y. Al-Fhady (Mesopotamia Journal of Agriculture)
Nine cultivars of durum wheat (Triticum durum Desf.) were tested for two years at Hammam Al-Alile on 1998 and 1999. Data on plant height, no. of days to heading and maturity,no. of spikes , no. of grains per spike ,1000 grain weight and grain yield were recorded and analysed for phenotypic and genotypic variances , heritability and correlations. Combine analysis exhibited significant differences between cultivars for all studied characters except grain yield. Cultivar X year interaction was significant for all studied characters except no. of days to maturity.High phenotypic and genotypic variances were found in plant height, no. of spikes , no. of grains per spike ,1000 grains weight and grain yield .Large environmental variability was observed in most characters except no. of days to heading and maturity and 1000 grain weight.High heritability estimations were found for all studied characters except grain yield and no. of days to maturity which gave low and moderate estimations respectively.Grain yield positively correlated with number of spikes in 98 and 1000 grain weight in two seasons.